Varietal wealth for enhancing tuber production - Devi, Asha; Sheela, A. M.N.; Mohan, C.; Anil, Shirly Raichal; Asha, K. I. (Indian Horticulture, 2019)
Of the 47 improved vareities of tuber crops, 12 varieties of cassava, 16 of sweet potato, 5 of greater yam, 3 of white yam, 2 of lesser yam, 6 of taro, 2 of elephantfoot yam and 1 of Chinese potato have been released by CTCRI, Thiruvananthapuram. Further, 8 new varieties are in pipeline for release. There are 3 varieties each of cassava and sweet potato, and 2 of greater yam to be released.